A Miniature Coxey's Army: The British Harvesters' Toronto-to-Ottawa Trek of 1924 - Cherwinski, W.J.C. (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1993)
A labour shortage in 1922, the promise of a bumper yield in 1923, and increased imperialist sentiment resulted in the recruitment of nearly 12,000 British workers to assist Canadian harvesters with the 1923 prairie wheat crop. Since most of them came from the cities they found the transition to western agriculture difficult and their complaints about the treatment they endured caused considerable damage to Canada's image abroad. Nevertheless, many persevered and returned home after the harvest satisfied. Those who remained to make a new life for themselves had a harder time since they were forced to take farm work at subsistence wages for the winter. Others chose to seek work in their own trades in Canada's cities. Like many, those in Toronto faced unemployment but, with the help of area radicals the militants amongst them decided to lead a long march to demand work at reasonable wages from the Mackenzie King government. Despite unrelenting harassment from public officials they remained united and with the assistance of citizens in the communities along the way they reached the capital bedraggled but defiant a fortnight later. While their march proved futile in the short term, it was an early example of escalating militancy among the unemployed, both domestic and immigrant, which helped to focus attention on both the plight of unskilled labour in a national economy and on the short-sighted, employer-driven immigration policies.